The influence of brand image and electronic word of mouth (eWOM) on the purchase decision of Hanasui lipstick cosmetics products - Burni, Annisa Nurjannah; Sari, Aida (Asian Journal of Economics and Business Management, 2025)
The cosmetics industry in Indonesia has experienced significant growth, particularly within the lipstick segment, marked by intense competition. Hanasui, a local lipstick brand, faces challenges in competing with prominent international brands such as Maybelline. This competitive landscape is evidenced by Hanasui's absence from the Top Brand Index in 2023. This study seeks to examine the impact of Brand Image and Electronic Word of Mouth (EWOM) on consumers' Purchase Decisions regarding Hanasui lipstick products in Bandar Lampung. Adopting a quantitative research approach, this study employs descriptive and verification analysis methods. Data were collected via online questionnaires distributed to 100 respondents in Bandar Lampung, selected through purposive sampling. The data were subsequently analyzed using the multiple linear regression method, facilitated by SPSS software. The findings reveal that both Brand Image and EWOM exert a positive and statistically significant influence on consumers' Purchase Decisions. Specifically, improvements in Brand Image and active management of EWOM significantly enhance consumer trust and decision-making regarding Hanasui products. The results underscore the importance of cultivating a strong brand image and leveraging positive electronic word-of-mouth to remain competitive in a highly saturated market. Based on these insights, it is recommended that Hanasui enhance its brand image through participation in promotional events, such as exhibitions, and engage professionally with online consumer reviews. These strategies are expected to build consumer confidence and foster higher purchase intentions, thereby improving Hanasui’s competitive position in the market.